2003
DOI: 10.1002/jbm.b.20003
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of acid etched titanium implants: Effect of sandblasting on bone anchorage

Abstract: The SLA (sandblasted with large grit and acid etched) surface is a textured surface that has been documented to lead to a rapid and strong implant fixation. The purpose of the present study was to determine the contribution of sandblasting in addition to etching to implant anchorage. It was also aimed to determine if the pits carved during etching alone have a bone-interlocking capacity that leads to microanchorage between the implant and bone. SLA implants and machined-and-acid-etched (MA) implants were place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
124
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 27 publications
(56 reference statements)
5
124
0
3
Order By: Relevance
“…In a study by Lincks and coworker 9 they roughened the titanium surface with blasting and acid etching, and reported that such a procedure increased the surface roughness and enhanced cell attachment and differentiation. Later on Szmukler-Moncler et al, 7 also reported a higher bone anchorage measured for the blasting and acid etching surface over the machined and just acid etched surfaces.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a study by Lincks and coworker 9 they roughened the titanium surface with blasting and acid etching, and reported that such a procedure increased the surface roughness and enhanced cell attachment and differentiation. Later on Szmukler-Moncler et al, 7 also reported a higher bone anchorage measured for the blasting and acid etching surface over the machined and just acid etched surfaces.…”
Section: Introductionmentioning
confidence: 90%
“…This retention of alumina may lead to the release some of these particles into the surrounding tissues and interfere with the osseointegration of the implants. 7,5 The benefit of blasting before acid etching has been questioned as it had been suggested that one of the advantages of acid etching in addition to increasing the surface roughness after grit-blasting was to clean and remove residual particles from the implant surface. In a study by Lincks and coworker 9 they roughened the titanium surface with blasting and acid etching, and reported that such a procedure increased the surface roughness and enhanced cell attachment and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, these approaches focused on the modification of the implant surface topography and morphology (17,18). These surface modifications mainly included mechanical methods such as machining (19,20), grinding, polishing (21) and blasting (22,23), and chemical methods such as acid etching (24,25), alkali etching (26,27) and anodization (28,29) to alter the topography of the titanium surface. Another approach towards the creation of a biologically active implant surface involves the application of an additional coating onto the titanium surface by means of physicochemical and biochemical deposition techniques (30,31).…”
Section: Surface Modification Of Titanium Implantsmentioning
confidence: 99%
“…Taking it a step further, not only is the implant material important, but the implant surface itself is also a critical factor in promoting osseointegration [9,10,11,12]. For example, titanium surfaces with microscale roughness have been shown to enhance osseous apposition by increasing the total surface area available for bone formation.…”
Section: Should Surface Tads Be Considered?mentioning
confidence: 99%
“…For example, titanium surfaces with microscale roughness have been shown to enhance osseous apposition by increasing the total surface area available for bone formation. In particular, a combination of sandblasting and acid-etching techniques has been effective in producing these microrough titanium surfaces [10,11]. Implants with sandblasted and acid-etched surfaces have increased osteoblastic attachment and differentiation, which in turn, have strengthened bone implant contact and enhanced removal torque values in biomechanical testing.…”
Section: Should Surface Tads Be Considered?mentioning
confidence: 99%